2019
DOI: 10.1002/ffj.3544
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization and biological activity of essential oils from the aerial part and root ofFerula haussknechtii

Abstract: Ferula genus belongs to Umbelliferae family. Plants with this kind of genus are distributed in an extended region such as central Asia and Mediterranean area. Ferula species are used in traditional medicine as a remedy in different kinds of illnesses and also in different kinds of industries. The Ferula haussknechtii H. Wolff ex Rech. f. is one of the flora species in Iran which in this research the essential oil of its aerial parts and root was extracted by Clevenger apparatus. After that, theirs compounds we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…EOs are considered as one of the well-known natural products which have medical-relevant use and biological-defense activities against several types of viruses, bacteria, and cancer 11 . However, the lack of the complete information about their intrinsic chemical variability and their function makes it difficult to confirm its consistent activities 4 . Many researchers have adopted the AI in EO's researches aiming to reduce the in-vitro procedures and to make reasonable predications of the experiment results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EOs are considered as one of the well-known natural products which have medical-relevant use and biological-defense activities against several types of viruses, bacteria, and cancer 11 . However, the lack of the complete information about their intrinsic chemical variability and their function makes it difficult to confirm its consistent activities 4 . Many researchers have adopted the AI in EO's researches aiming to reduce the in-vitro procedures and to make reasonable predications of the experiment results.…”
Section: Discussionmentioning
confidence: 99%
“…The biological activities of the EOs may include antiseptics, antimicrobials, antifungals, antioxidant, antitumor, antivirals, and/or anti-inflammatories. Moreover, these activities vary according to the chemical constitution, which may differ from plant to another according to their geographic location, agriculture conditions, climatic or seasonal changes 4 . Noteworthy, the evaluation of the EOs' bioactivities cannot be constantly credited to one single compound in the EOs mixture.…”
mentioning
confidence: 99%
“…The F. haussknechtii essential oil, which was extracted by the Clevenger apparatus contained camphene, α-pinene, and isoverbanol as abundant chemical constituents; these compounds exhibited antibacterial activity against nine bacterial strains. The result showed that Bacillus pumilus, Staphylococcus epidermidis and S. aureus were more sensitive to the essential oil among other tested bacterial strains (Arjmand and Dastan, 2020). Alipour et al, (2015) enumerated the bactericidal activity of the essential oil acquired from stem, leaf, and flower parts of the Ferula cupularis Boiss.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Generally, aromatic acid lactones sesquiterpenes, coumarins, and sesquiterpene coumarins are present in the roots of Ferula species (Teng et al, 2013), whereas monoterpenes, oxygenated monoterpenoids sesquiterpenes and oxygenated sesquiterpenoid are the main chemical constituents of essential oil present in the aerial parts of Ferula (Mohammadhosseini et al, 2015). Due to the widespread therapeutic effects of this genus, it is being used in folk medicine to treat a variety of diseases and disorders, including skin infections, psychiatric disorders (especially seizure), hyperlipidemia, diabetes, arteries sclerosis, digestive disorders (dysentery), osteoporosis, arthritis, HIV, influenza type A, cancers (uterine cancer), muscle relaxant, rheumatism, headaches, hypertension, toothache and dizziness (Zhou et al, 2017;Meena et al, 2018;Arjmand and Dastan, 2020;Esmaeili et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For nonvolatile phytochemical analysis of the methanolic extract was carried out using standard procedures to identify of the existence or nonexistence of various constituents such as saponins, alkaloid, flavonoid, terpenoids, tannins, phlobatannin, steroid, phenols proteins, carbohydrate, proteins and glycosides compounds [21][22].…”
Section: Non-volatile Phytochemical Screeningmentioning
confidence: 99%